2011
DOI: 10.2478/v10182-011-0011-6
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol For Synthetic Seeds From Salvia Officinalis L. Shoot Tips

Abstract: Shoot tips excised from shoot culture of Salvia officinalis were encapsulated in 2% or 3% (w/v) sodium alginate and exposed to 50 mM calcium chloride for complexation. Immediately or after 6, 12 or 24 weeks of storage at 4°C, the synthetic seeds were cultured for 6 weeks on half-strength MS medium supplemented with indole-3-acetic acid (IAA) (0.1 mg/l) and solidified with 0.7% agar. The frequency of shoot and root emergence from encapsulated shoot tips was affected by the concentrations of sodium alginate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This explains increasing the regrowth percentage of propagules coated with MS containing matrixes. The inclusion of sucrose in the alginate matrix also improved the regrowth percentage from encapsulated shoot tips of Camelia japonica and axillary buds of Betula pendula (Grzegorczyk and Wysokinska, 2011). Rai et al (2008) proved that; the emergence of shoots from encapsulated shoot tips of Psidium guajava was completely inhibited in medium lacking sucrose.…”
Section: Table (1) Effect Of Storage Temperature and Alginate Matrixmentioning
confidence: 84%
See 1 more Smart Citation
“…This explains increasing the regrowth percentage of propagules coated with MS containing matrixes. The inclusion of sucrose in the alginate matrix also improved the regrowth percentage from encapsulated shoot tips of Camelia japonica and axillary buds of Betula pendula (Grzegorczyk and Wysokinska, 2011). Rai et al (2008) proved that; the emergence of shoots from encapsulated shoot tips of Psidium guajava was completely inhibited in medium lacking sucrose.…”
Section: Table (1) Effect Of Storage Temperature and Alginate Matrixmentioning
confidence: 84%
“…This demonstrates that, MS medium plays a vital role and considers an important ingredient in Na-alginate matrix for regrowth. Piccioni and Standardi (1995) and Grzegorczyk and Wysokinska (2011) reported that; the addition of MS to the alginate matrix led to reduction in the gel viscosity. This explains increasing the regrowth percentage of propagules coated with MS containing matrixes.…”
Section: Table (1) Effect Of Storage Temperature and Alginate Matrixmentioning
confidence: 99%
“…Even it was reported that the high concentration or the long exposure of the embryos to the calcium chloride results in more absorption and penetration of CaCl2 in the embryo, which can lead to growth inhibition [21]. But based on Fig.2, it can be seen that the percentage of germination of synthetic chrysanthemum seeds showed that there were not significantly different at each storage period.…”
Section: A Encapsulationmentioning
confidence: 87%
“…This suggests a significant impact of genetic factors on this trait. Perhaps the addition of auxins or gibberellic acid (GA 3 ) to the artificial endosperm could improve rooting in bleeding heart, as reported with synthetic seeds of Salvia officinalis L. [32].…”
Section: Morphogenetic Response Of Explantsmentioning
confidence: 97%